Benign metastatic leiomyoma: pulmonary and cerebral involvement - Alves,Mariana Carlos (2018)
Benign metastatic leiomyoma (BML) is a rare disorder characterized by the presence of extrauterine leiomyomatous lesions. The authors report a case of a 70-year-old woman with previous total hysterectomy for uterine leiomyoma, that presented with dry cough and a history of progressive weight loss. Thorax computerized tomography revealed multiple nodular masses, suggestive of pulmonary metastases. The immunohistochemical study showed that the diagnosis was compatible with BML. The patient then presented a nodular brain lesion suspected of metastasis but died before the biopsy for etiologic confirmation.